CRITICAL REFLECTION ON PRACTICE DEVELOPMENT Facilitating person-centred leadership support during the Covid-19 crisis. (17th November 2021) - Hølge-Hazelton, Bibi; Rosted, Elizabeth; Borre, Line Zacho; McCormack, Brendan; Kjerholt, Mette
No abstract available